Revised Statutes of the State of Arkansas, Adopted at the October Session of the General Assembly of Said State 733-34 (1838) - (:unkn) unknown (General Publisher, 1837)
Prohibited “any slave” from possessing any gun or weapon without written permission from their master.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES